2013
DOI: 10.1177/0040517513509850
|View full text |Cite
|
Sign up to set email alerts
|

Fibers susceptibility to contamination by environmental tobacco smoke markers

Abstract: Textiles are characterized by a diversified and relatively high susceptibility to sorption of volatile substances and may influence indoor air quality. The aim of this study was investigation the susceptibility of fibers to sorption of two environmental tobacco smoke (ETS) markers: nicotine and 3-ethenylpyridine (3-EP) and changes in concentrations of these substances in fibers under light exposure. For this purpose, we used non-colored, natural and synthetic fibers, which had not been subjected to any modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The photocatalytic properties were tested by the decomposition of nicotine adsorbed on cotton and viscose fabrics modified with TiO 2 -anatase. The testing was performed at 21 ± 2°C on the test stand as previously described (Cieslak et al 2009;Cieslak et al 2014). Briefly, ten samples of each fabric type were hung in a chamber (40 dm 3 ) and the chamber air was evacuated; 5 ll of nicotine (Fluka 72290, CAS 54-11-5, puriss.…”
Section: Characterizationmentioning
confidence: 99%
“…The photocatalytic properties were tested by the decomposition of nicotine adsorbed on cotton and viscose fabrics modified with TiO 2 -anatase. The testing was performed at 21 ± 2°C on the test stand as previously described (Cieslak et al 2009;Cieslak et al 2014). Briefly, ten samples of each fabric type were hung in a chamber (40 dm 3 ) and the chamber air was evacuated; 5 ll of nicotine (Fluka 72290, CAS 54-11-5, puriss.…”
Section: Characterizationmentioning
confidence: 99%
“…Sorption and decomposition of nicotine on the fibers are affected by the physicochemical characteristics of the sorbate and the textile and non-textile sorbents (Cieślak et al 2014;Cooks 1999;Banyasz 1999;Gregg and Sing 1967;Adamson and Gast 1997), and they also depend on the ambient conditions under which these processes occur (Weschler and Nazaroff 2008). Nicotine is a bicyclic alkaloid characterized by amphiphilic properties, because its molecule possesses both a hydrophilic and a hydrophobic part.…”
Section: Mechanism Of Sorption and Decomposition Of Nicotinementioning
confidence: 99%
“…Furnishing textile materials constitute a significant element in different rooms: residential, office, public buildings or means of transport. Textile materials, because of their specific character, can affect the content of volatile pollutants in the indoor air, including the constituents of tobacco smoke (ETS-environmental tobacco smoke) (Piade et al 1999;Cieślak 2006;Cieślak and Schmidt 2004;Chien et al 2011;Cieślak et al 2014). The susceptibility of sorption of ETS markers in seven types of fibers was tested, and it was found that polypropylene fibers have a particularly high susceptibility for the sorption of nicotine, which is a highly addictive component and the main marker of ETS (Cieślak et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Handloom Textile materials, because of their specific characters and affect the content of volatile pollutants in the environment, including constituents of tobacco smoke The susceptibility of sorption was tested and it was found cotton fabric has the susceptibility of absorption nicotine, which is a highly addictive component [1].…”
Section: Introductionmentioning
confidence: 99%